Regulasi Diri Anak Usia 5-6 Tahun Dalam Mengikuti Kegiatan Belajar Daring Di Tk Pembina - Efni Juniarti; Susi Herlinda; Herwina (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2021)
The problem of this research is that the self-regulation of children who take part in online learning activities has not yet achieved the development as expected. The purpose of this study was to determine the self-regulation of children aged 5-6 years in participating in online learning activities at the Pembina Kindergarten. The type of research is descriptive qualitative. The subjects of this study were parents of children aged 5-6 years totaling 8 people. The results of this study are that the attitude of children in managing themselves to always participate in online learning activities is good. The conclusion of this study is that children's self-regulation is classified as good, it can be seen that children are able to organize and plan their online learning activities well. As early childhood self-regulation is seen from metacognitive indicators, motivation and behavior that show they are good in participating in online learning activities. The advice given in this study is to schools to further enhance collaborative efforts between teachers and children's parents in online learning activities and improve children's self-regulation in learning.